THE ANALYSIS OF DRUGS SITUATION IN MARI EL REPUBLIC - A. I. Sidorkin (Russian Journal of Economics and Law)
The article views the drugs situation in the Republic of Mari El in 2005 and 2006. usingthe statistical method on various aspects, the author analyzes the dynamics of the population narcotization. The author also suggests a number of activities which could help to regulate the drug situation in Mari El Republic, as well as in whole Russia.